High-Throughput Screening by In silico Molecular Docking of Eryngium Foetidum (Linn.) Bioactives for Cylcooxygenase-2 Inhibition - Rangahanumaiah, Pavan; Rai, Ravishankar Vittal; Saqhib, Asma; Jothi, Lydia; Swamy, Marula Siddha; Karigar, Chandrakant Shivappa; Sekhar, Shailasree (Pharmacognosy Communications)
Several studies are in progress worldwide to find natural healing agents with better safety profiles. Our current study aimed to screen and evaluate Eryngium foetidum Linn. bioactives reported for therapeutic drug discovery by In silico docking. Ligands /bioactives were prepared by following the appropriate procedures and finally In silico molecular docking to cyclooxy- genase (COX)-2 was performed and analyzed by FleX X. Of the docked bioactives, caryophyllene oxide in particular, showed high binding affinity of -7.00 kcal/mol against 1PXX corroborating in vitro COX-2 inhibition and providing a theoretical contribution in understanding the ligand-protein interactions. The docked pose resembled the orientation similar to that observed with diclofenac ligand (inhibitor of COX-2). The ligand was docked deeply within the binding pocket region forming interactions with ALA527GLY526LEU352SER530TYR348TRP387VAL349VAL523 and Ser353. Our docking result was found to have three hydrogen bonding sites with SER530TYR348 and TYR385, indicating COX-2 inhibition with the highest fitness score of 50.64. Furthermore, all the bioactives were subjected to iLOG predictor of the Swiss ADMET website software generating In silico ADME properties and testing their capacity to exhibit drug likeliness. The data supports caryophyllene oxide to be a potent anti-inflammatory com- pound worthy of further clinical trials.
Keywords: Eryngium foetidum; Swiss Dock; cyclooxygenase-2 inhibitor; iLOG predictor of the Swiss ADMET; Caryophyllene oxide.